Upaya Meningkatkan Prestasi Belajar IPA Pada Materi Sifat Sifat Benda Melalui Penerapan Metode Pembelajaran Demonstrasi Pada Siswa Kelas III SDN 013 Tambusai Utara Tahun Ajaran 2013/2014 - Barma Juita (Indonesian Journal of Basic Education, 2018)
IPA is a subject studied by students of Class III SD. One of the science materials that is difficult to understand students in Class III SD is the Nature of Nature. The low understanding of the students on the properties caused by the students have difficulty in understanding the material presented by the teacher. Teachers speak more, so students are not actively involved in learning and it is difficult to get a deep understanding. This affects the low learning outcomes of students on the material properties. The essence of IPA is the IPA as a product, attitude, and process. With IPA science teaching is not only giving priority to the concept of IPA concept, but it needs to involve the five senses of students maximally. One effort that can be done to overcome the low achievement of third grade students of SD on the material properties by maximizing the five senses of students is the method of demonstration. The problem in this research is "Efforts to Increase the Achievement of Science Learning in Material Properties Through the Application of Demonstration Learning Methods in Students Class III SDN 013 Tambusai Utara Tahun Ajaran 2013/2014" Method of demonstration is a teaching method that presents lesson material by showing the subject directly or how to do something, so students learn the subject matter through a series of processes Based on the discussion and research results. So it can be concluded that within a period of approximately 2 weeks, with the concept of 4X meeting then the method of demonstration has a positive impact on the process of learning science subjects, especially on the material properties. This method is very suitable in applied to students. With demonstration methods students can more easily understand and practice what is taught by the teacher